Novel use of a Sengstaken–Blakemore tube during a neck exploration of a carotid injury: A case report. Issue 9 (September 2016) - Bensley, Rodney P.; Mohr, Alicia M.; Huber, Thomas S.; Sappenfield, Joshua W.
Abstract: Penetrating neck trauma can injure the major blood vessels, airway, gastrointestinal system, and neurological system. We present a case where a Sengstaken–Blakemore tube was emergently placed during surgical exploration of a stab wound to the neck to tamponade bleeding until surgical control was obtained and the vascular injuries were managed.